(untitled) (Research, Society and Development, 2021)
Commonly known as fall armyworm Spodoptera frugiperda is one of the most important agricultural pests in Brazil, due to its polyphagous habit and its wide geographical distribution. The use of entomopathogenic agents has contributed to the management of this pest, as it reduces the impacts caused by agrochemicals and provides sustainable agriculture. The aim of this work was to evaluate the pathogenicity of the entomopathogenic bacteria Bacillus thuringiensis and the entomopathogenic virus Nucleopolyhedrovirus (HearNPV) when applied directly to the caterpillar S. frugiperda. The experiment was carried out with 2nd and 3rd instar caterpillars. Each experiment had 5 treatments: T1: Control (without entomopathogen application), T2: Agree®, T3: Xentari®, T4: Diplomata®; T5: Armigen®, and 5 repetitions per treatment, each repetition containing 6 caterpillars of 2nd and 3rd instar. Each repetition consisted of a Petri dish (9 cm in diameter) with 1 insect, totaling 30 caterpillars of each instar per treatment. Mortality was assessed daily up to fifteen days after application. The accumulated mortality data were submitted to analysis of variance (F test), the averages will be compared by the Scott-Knott test at 5% probability and the efficiency of the insecticides by the Abbott formula. The bioinsecticide Xentari® provided a higher mean of mortality in the 2nd instar of S. frugiperda differing from the other treatments, in the 3rd instar there was no significant difference between treatments.